INOVASI DALAM PEMBELAJARAN SAINS MASA DEPAN MELALUI STEM (SCIENCE, TECHNOLOGI, ENGINEERING, AND MATHEMATIC) EDUCATION DI SMA MUHAMMADIYAH 3 JEMBER - Alvi Maulidia; Lailatul Nuraini; Albertus Djoko Lesmono (Universitas Jember, 2020)
This article discusses how to find out the level of student creativity in science learning, using the PBL (Problem Based Learning) learning model through the STEM approach (Science, Technology, Engineering, and Mathematics). The goal is to use these learning students who have different thought patterns and levels of creativity can process their thoughts with different outputs on the cognitive domain of students in learning physics in the material elasticity and hooke law in class XI Mipa 3 students at Muhammadiyah 3 High School Jember The data obtained in the form of worksheets (Student Worksheets) and the final product. This type of research uses true experimental research. The instruments needed in this research are test sheets. The results of this study are that using the STEM approach can provide innovative thinking for high school students' creativity in mastering physics learning.